The VEGPREV study: effectiveness of four plant-based diets on weight loss, metabolic syndrome components and appetitive traits in overweight and obese individuals: a randomized controlled trial - Wiśniewska, Klaudia; Okrȩglicka, Katarzyna Małgorzata; Paskudzka, Monika; Jagielska, Anna Maja; Bober, Julia; Oczkowski, Michał; Ciepiela, Olga; Nitsch-Osuch, Aneta (Frontiers in Nutrition, 2025)
BackgroundObesity and its associated metabolic disturbances remain a growing public health concern, highlighting the need for effective and sustainable dietary strategies. This randomized controlled trial aimed to compare the effects of four plant-based dietary patterns: vegan (VG), lacto-ovo-vegetarian (LOV), Mediterranean (MD), and the EAT-Lancet Planetary Health Diet (EAT) with a control diet based on WHO recommendations (CTRL) in reducing body weight and improving selected metabolic and behavioral parameters in overweight and obese adults.MethodsA total of 90 participants (aged 18–64) were methodically assigned to one of five distinct dietary groups for a period of 12 weeks. The primary outcome measured was the change in body weight. Secondary outcomes encompassed body composition, waist circumference, energy and macronutrient intake, fasting plasma glucose and insulin levels, arterial blood pressure, plasma lipid profile, appetitive traits, physical activity, and quality of life. A total of 85 subjects completed the intervention.ResultsAll plant-based diets resulted in a reduction of body weight, waist circumference, fat mass, and energy intake in comparison to the control group. The most pronounced body weight reductions were observed after 12 weeks in the VG group (−6.7%) and the EAT group (−5.6%) (p < 0.001). A significant decrease in fat mass was observed across all intervention groups (p < 0.01). The investigation revealed no substantial between-group disparities in fasting plasma glucose, insulin, HOMA-IR, lipid levels, blood pressure or appetitive traits. No serious adverse events were observed.ConclusionAmong plant-based dietary patterns differing in animal product content, the EAT and VG diets demonstrated the most pronounced effects on weight and body composition. These findings provide support for the notion that structured, plant-based dietary interventions can be effective strategies for managing body weight.